Liquid Organic Fertilizer From Biogas Liquid Waste with The Addition of Rabbit Urine, Monosodium Glutamate and Water Hyacinth - Anis Aziza Zumroturrida; rosita dwityaningsih; Dodi Satriawan; Oto Prasadi (Jurnal Loupe, 2024)
Biogas liquid waste has the potential to be used as a base material for liquid organic fertilizer due to the potential for its fairly high organic compund content. Rabbit urine and water hyacinth are known to contain material that are used for plants.MSG ia a cooking spice that contains sodium salt (Na) which is bound to amino acids in the form of glutamate, with Na element being able to improve plants that deficient in potassium (K).The aim of this research is to process liquid biogas waste into liquid organic fertilizer (POC) by adding water hyacinth, rabbit urine, and MSG using an anaerobic process. The results of this research showed that the control POC contained 0.067% N, 0.27% P2O5 and 0.023% K2O. POC A 0.056% N, 0.27% P2O5 and 0.32% K2O. POC B 0.022% N, 0.32% P2O5 and 0.11% K2O.